Effect of industrial work experience in developing Technical and Vocational Education undergraduates’ employability skills - Okoye, Kelechi Reko; Edokpolor, James Edomwonyi (Asian Journal of Assessment in Teaching and Learning, 2021)
This study aims to assess the effect of industrial work experience in developing employability skills among technical and vocational education undergraduates in Nigerian universities. Data were collected from 119 undergraduates of technical and vocational education (TVE) with a pre-and post-survey instrument. When compared with a paired sample t-test, the result showed that the employability skills possess by TVE undergraduates before and after exposure to industrial work experience significantly differ. When compared with the independent sample t-test, the result showed that the employability skills possess between male and female TVE undergraduates before exposure to industrial work experience does not significantly differ. When also compared with independent sample t-test, the result showed that the employability skills possess between male and female TVE undergraduates after exposure to industrial work experience significantly differ. This study has contributed to the existing literature concerning the effect of industrial work experience in developing employability skills among technical and vocational education undergraduates. This unique contribution would provide a better insights or understanding on how industrial work experience scheme help in developing employability skills among technical and vocational education undergraduates.